The Chorus of Trojan Women in Hecuba: searching for the Meaning of War - Navarro Noguera, Andrea (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2022)
In Euripides’ tragedy Hecuba, the chorus is formed by captive Trojan women who serve the double purpose of enhancing their old queen’s intense emotions and revealing, as victims, the consequences of a war that has sowed destruction and loss among victors and vanquished. Bearing in mind this belligerent context and its effects on the population, I propose to focus on a special selection of stasima, to examine the chorus as a mediating element in the development of the tragedy, and to show how the evolution of this collective character, in parallel with that of the central heroine, facilitates a holistic understanding of the entire play.